2014
DOI: 10.4049/jimmunol.1302961
|View full text |Cite
|
Sign up to set email alerts
|

Adult Thymic Epithelium Contains Nonsenescent Label-Retaining Cells

Abstract: Progress in our understanding of thymic epithelial cell (TEC) renewal and homeostasis is hindered by the lack of markers for TEC progenitors. Stem and progenitor cell populations display remarkable diversity in their proliferative behavior. In some but not all tissues, stemness is associated with quiescence. The primary goal of our study was to discover whether quiescent cells were present in neonatal and adult TECs. To this end, we used a transgenic label-retaining cell (LRC) assay in which a histone H2B-GFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 51 publications
7
56
1
Order By: Relevance
“…The absolute numbers of cTECs decline rather rapidly during the neonatal period, whereas mTECs increase (Supplemental Fig. 2A) (29). Consistent with this age-dependent decline in cTECs, we observed that the total numbers of Aire + cTECs from b5t/Aire-Tg mice declined with age (Fig.…”
Section: Epcamsupporting
confidence: 82%
“…The absolute numbers of cTECs decline rather rapidly during the neonatal period, whereas mTECs increase (Supplemental Fig. 2A) (29). Consistent with this age-dependent decline in cTECs, we observed that the total numbers of Aire + cTECs from b5t/Aire-Tg mice declined with age (Fig.…”
Section: Epcamsupporting
confidence: 82%
“…Although the functional importance of this effect has yet to be demonstrated, we propose that it may contribute to the dramatic changes in TEC subsets that occur in the neonatal period: expansion of the mTEC compartment in the first weeks of life is accompanied by an abrupt decrease in the number of cTEC (19). Therefore, although cTEC are the dominant TEC subset at birth, they represent only 10% of TEC in adults (60). Moreover, we confirmed that the impact of AIRE-dependent pGE is not limited to generation of TRA.…”
Section: Discussionmentioning
confidence: 91%
“…We next addressed whether the reduction in TEC numbers might reflect a specific decline in the mTEC or cTEC compartment. The abundance of cTECs peaks around birth, whereas the frequency of cTECs in young adult mice is low (34). Therefore, we also analyzed the mTEC/cTEC ratio in newborn mice (P3) and found that it was not affected in FoxN1-Gpr177 mice (Supplemental Fig.…”
Section: Foxn1-gpr177 Tecs Have a Higher Apoptosis Rate But Proliferamentioning
confidence: 99%